Long non-coding RNA PVT1: A promising chemotherapy and radiotherapy sensitizer - Yao, Weiping; Li, Shuang; Liu, Ruiqi; Jiang, Mingyun; Gao, Liang; Lu, Yanwei; Liang, Xiaodong; Zhang, Haibo (Frontiers in Oncology, 2022)
The long non-coding RNA (lncRNA) PVT1 was first found to activate variant translocations in the plasmacytoma of mice. Human lncPVT1 is located on chromosome 8q24.21, at the same locus as the well-known MYC oncogene. LncPVT1 has been found to promote the progression of various malignancies. Chemoresistance and radioresistance seriously affect tumor treatment efficacy and are associated with the dysregulation of physiological processes in cancer cells, including apoptosis, autophagy, stemness (for cancer stem cells, CSC), hypoxia, epithelial–mesenchymal transition (EMT), and DNA damage repair. Previous studies have also implicated lncPVT1 in the regulation of these physiological mechanisms. In recent years, lncPVT1 was found to modulate chemoresistance and radioresistance in some cancers. In this review, we discuss the mechanisms of lncPVT1-mediated regulation of cellular chemoresistance and radioresistance. Due to its high expression in malignant tumors and sensitization effect in chemotherapy and radiotherapy, lncPVT1 is expected to become an effective antitumor target and chemotherapy and radiotherapy sensitizer, which requires further study.